Occupational therapy and transgender persons: the impacts of social collection on gender (Research, Society and Development, 2021)
The role of men and women in society is defined by their sexual organs, however, people who do not fit in and identify themselves as being of the opposite gender question this concept, trans people. The collection of behavior and body image can affect mental health and social life. Occupational therapy works in different contexts in the care of transgender people who sometimes face difficulties in their relationships and in social environments. General objective: to understand and report the social and mental impacts of the notions of gender on trans people, through expressive activities used in the meeting of occupational therapy. Specific objectives: to understand the greatest difficulties and / or prejudices faced by trans people in their childhood and current society; understand how social oppression affects their mental health and what they crave for that improvement and describe their understanding of family, love and their expectations for the future. The methodology of the research is qualitative, with discourse analysis, which were carried out in a meeting, with a group of trans people, with diverse themes. It was possible to perceive that prejudice runs through the whole life of these people, causing them to experience situations of repression and violence from childhood, generating the fear and the need to fight for their very existence and for the freedom to be happy being who, society has a fundamental role in the lives of these people, and can be a risk or protection factor.